Weird But True! World 2024 - Incredible Facts, Awesome Photos, and Weird Wonder for this Year and Beyond! World, 2024 (Washington, DC : National Geographic, 2023)
"Discover Earth's strangest natural wonders, animals, festivals, ancient architecture, news, and more in this annual compendium of everything Weird But True! fans love--and then some. Readers will journey across the seven continents, dive into the ocean, and even blast off into space to discover a whole wide world of weird. From volcano-surfing in Nicaragua to a beach in Japan where the 'sand' is shaped like stars to extreme ironing competitions in the United Kingdom, Weird But True! World offers an ... adventure-filled exploration of our world's amazing uniqueness"--
Weird this year -- Incredible North America -- Spectacular South America -- Unique Europe -- Awesome Africa -- Astounding Asia -- Outstanding Australia & Oceania -- Amazing Antarctica -- Sensational sea & space.
Keywords: Curiosities and wonders -- Juvenile literature; Curiosities and wonders; Curiosities and wonders; Trivia and miscellanea; FAQs; Juvenile works